2011
DOI: 10.1016/j.ajpath.2010.10.023
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Suppresses Expression of the Urea Cycle Enzyme Carbamoyl Phosphate Synthetase 1 (CPS1) in Human Hepatocellular Carcinoma

Abstract: Carbamoyl phosphate synthetase 1 (CPS1) is a liverspecific, intramitochondrial, rate-limiting enzyme in the urea cycle. A previous study showed that CPS1 is the antigen for hepatocyte paraffin 1 antibody, a commonly used antibody in surgical pathology practice; and CPS1 expression appears to be down-regulated in liver cancer tissue and cell lines. The aim of this study is to understand how the CPS1 gene is regulated in liver carcinogenesis. In this report, we show that human hepatocellular carcinoma (HCC) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 28 publications
4
80
1
1
Order By: Relevance
“…CPS1 is expressed mainly in intestinal epithelial cells and liver cells, as well as several types of cancer including liver, colorectal, stomach, cervical, and pancreatic cancer (29)(30)(31)(32)(33)(34)(35)(36)(37). Although expression of CPS1 protein has not been well studied in lung cancer, Kaufman ARTICLE (38).…”
Section: Discussionmentioning
confidence: 99%
“…CPS1 is expressed mainly in intestinal epithelial cells and liver cells, as well as several types of cancer including liver, colorectal, stomach, cervical, and pancreatic cancer (29)(30)(31)(32)(33)(34)(35)(36)(37). Although expression of CPS1 protein has not been well studied in lung cancer, Kaufman ARTICLE (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, P4501A1 inducibility, which does not rely on CPS1, confirmed that AhR functionality persisted over the 3-week culture period. In complementary studies, CPS1 expression was re-established in AML12 cells using 5-aza-2Ј-deoxycitidine (5-Aza) to hypomethylate the CPS1 promoter (24). TCDD-inducible hcit formation only occurred in the 5-Aza-treated CPS1-positive cells (Fig.…”
Section: Cps1 Is Required For Nuclear Proteinmentioning
confidence: 99%
“…Epigenetic biomarkers based on promoter hypermethylation have been developed as diagnostic tools to detect liver cirrhosis and HCC (Table 1). 410 Many studies have shown that progressive promoter methylation accumulates throughout HCC development and is associated with tumor recurrence and prognosis. 27, 28, 3032 …”
Section: Hepatocellular Carcinoma As a Cimp+ Cancermentioning
confidence: 99%
“…410 Many of the DNA methylation biomarkers identified distinguish between normal healthy tissue and cirrhotic tissue, however the distinction between cirrhotic tissue and HCC is less clear. Many gene promoters which are methylated in HCC are also methylated in the surrounding cirrhotic tissue (Table 1).…”
Section: Hepatocellular Carcinoma As a Cimp+ Cancermentioning
confidence: 99%
See 1 more Smart Citation